(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Amongst all fractures around elbow in children second most common is the lateral condylar fracture, commonly occurring in 6-10 years age group, contributing up to 5-20% of elbow fractures. Rotated and displaced fractures obviously require proper reduction and stabilization. Objective: For evaluation of the results of open reduction internal fixation as the main treatment option. Methods: We observe 30 children treated with ORIF at CMH, Bogura, out of them 25 male and 5 female. 2mm or more displaced fractures were included into the study group, demographic data and radiographs were taken from February 2017 to January 2019. Average age was seven years. 25 were Milch type ll and 5 Milch type l. Fractures were managed with ORIF with two smooth k-wire of 2mm in diameter. Results: Mean time of union was 4.7 weeks, k-wire removal on 36 days, and follow up period was 16.5 months. Two (6.66%) patient suffered with superficial wound infection which was treated by oral antibiotics. One (3.33%) develop 100 loss of humeroulnar motion. Four (13.33%) develop lateral spurring followed by one (3.33%) individual developed pseudo cubitus varus deformity. There were no other complications like malunion, nonunion, AVN, deep wound infection, cubitus valgus or varus deformity. According to Hardacre et al criteria 29(96.66%) patient reached excellent final result, 1(3.33%) achieved good result. Conclusion: For displaced lateral condylar fracture open reduction internal fixation has excellent functional outcome. JAFMC Bangladesh, Vol 20, No 1 (June) 2024: 34-36